MAIN ECONOMIC PROBLEMS AND THEIR SOLUTIONS - Turayeva Malika Khikmatovna; Djuraeva Makhzuna Azamovna (Scholar Express Journals, 2023)
In the article basic problems which we come across in economy field nowadays are noted. In addition to this the ways of overcoming economic problems and finding solutions are highlighted.
Keywords: Macro-economic decisions; market economy; products